OPPORTUNITIES FOR TOURIST CONECTION MUNICIPALITIES MALI ZVORNIK AND ZVORNIK, AS A FORM OF STRENGTHENING CROSS-BORDER COOPERATION BETWEEN SERBIA AND BOSNIA & HERCEGOVINA - Predrag Vuković; Nataša Cecić; Slavica Arsić (Ekonomika Poljoprivrede (1979), 2011)
The paper insists on the fact that it is necessary that the municipality of Zvornik in Bosnia and Mali Zvornik in the Republic of Serbia, acting in the market as a unique tourist destination. In this sense, emphasis is placed on complementarity in all marketing and strategic management steps, policies, plans and organization of tourism. The priority goal ahead of the two brotherly municipalities, is to clearly present the natural and anthropogenic resources to enrich the tourist with adequate performance and organization. The emphasis of the offer must be placed in an appropriate quality of service and marketing and management approach as an imperative request, to market resources and valorise. It is necessary that declarative long-standing support for the development of tourism practically comes to life and multiplied the effects that tourism brings to the overall economic and social life, it is realistic to expect investors will quickly return.